Strategic spatial planning. A historical review of approaches, its recent revival, and an overview of the state of the art in Italy. - Sartorio, Francesca S. (TH Zürich, ORL-Institut, 2005)
Der in drei Abschnitte gegliederte Beitrag beginnt mit einer Übersicht über die zahlreichen Varianten Strategischer Planung der letzten zwanzig Jahre, stellt dabei die Inkonsistenz des Strategiebegriffs fest, um sich dann speziell der Entwicklung der strategischen Planung im Italien des letzten Jahrzehnts zuzuwenden. Der letzte Abschnitt stellt das kreative Potenzial der strategischen Planung in Italien vor: Die erste kreative Dimension strategischer Planung liegt in der Schaffung von neuen Räumen, von Synergien im Raum, gerade in Metropolen und Großstadtregionen, in der Überwindung fester administrativer Grenzen. Die zweite Dimension strategischer Planung liegt in der Herstellung von Local Governance durch die Gestaltung von kooperierenden Prozessen der Akteure aus Wirtschaft und Verwaltung. oc/difu

The last century left us with various definitions and interpretations of strategic spatial planning. What seems clear today is that strategic planning could he considered a set of concepts, procedures and tools, usefully adaptable to fit the current planning needs of modern states and local societies in Europe. At the beginning of the 1990s, many experiences from all over the continent caught the interest of theorists and practitioners and started a long debate on the revival of strategic spatial planning. If we look at the practices though, it is evident that the approaches and goals are diverse and inevitably strongly related to specific local contexts. During the last decade, a particularly significant one for Italy due to the many social and institutional changes, several metropolitan areas and city-regions have been experimenting with strategic plans. These plans are aimed at encouraging local actors to get together and develop shared visions for the future. Even if a few common features are recognizable in all these plans, each of these tools is context-specific and develops particular procedures aimed at specific goals. An evaluation of this fruitful endeavour is not yet unequivocally possible, but the creative potential of these informal tools is already evident in the discovery of new actors and forms of local action, the development of local governance at variable geometries and in fostering local endogenous seeds of development. difu
Keywords: Raumplanung; Stadtentwicklungsplanung; Regionalplanung; Planungstheorie; Planungsprozess; Stadtplanung; Kreativität; Planungsstrategie; Governance; Local Governance